TINGKAT PARTISIPASI MASYARAKAT TERHADAP KEPEMILIKAN AKTA TANAH (Studi Di Desa Bale Kecamatan Bukit Kabupaten Bener Meriah Provinsi Aceh) - Zefri Noci Vera (PERSPEKTIF, 2016)
Community participation is needed of the ownership of land, current land position in accordance with the development, the land is a means to carry out the construction, agricultural land, industry, and trade. The problems proposed in this research is "How tinggkat public participation in the ownership of the land deed in the village of Bale" and "Factors that influence the level of public participation in the ownership of the land deed" Results of research and discussion to explain the level of participation of rural communities Bale extremely high participation in the activities of the land deed registration, there are some society participation in the follow land registration activities, namely: participation in the direct involvement, community participation of individuals, participation in the form of support. It can be concluded that community participation is very important in the possession of the land deed.